Analysis of Student Satisfaction with University Management Services - Suherman, Agus; Inoe, Hiromu (FKIP Universitas Lampung, 2025)
Analysis of Student Satisfaction with University Management Services. Introduction: This study aimed to determine and measure student satisfaction with the quality of services at Syekh-Yusuf Islamic University, adapting a service quality model by incorporating an additional dimension,